Waterscape: users perceptions as a tool for the development of urban guidelines at Poti and Parnaíba's reverbanks and surroundings - Matos, Karenina Cardoso; Veloso, Maísa Dutra (Paisagem e Ambiente, 2007)
Assuming that waters have a strong power of attraction on the cities and their users, this research tries to assess the relation between the water landscape and Teresina city, regarding four conceptual axes: the water landscape, the perception of the users, the rivers as strength lines and the power of attraction througt natural, constructed and symbolic elements of the landcape. The structuring axes enabled the reading of the sceneries, according to the delimited area which comprises two original nuclei of the city: bairro Poti Velho and the center of Teresina, in such a way as to show visible and/or non-visible, valued or nonvalued aspects, so as to provide subsidies for the designing of guidelines and interventions of urban planning of Teresina city, more particularly in the region being studied. The elements were revealed, characterizing today the depreciation of the rivers within the landscaping, geographic, economical, cultural and environmental conditions analyzed; trere area potentialities; but there are also obstacles and threats to the landscaping structure and the quality of the riverside population; convergences and divergences can be noticed in the water landscape. However, this work is expected to constitute a referential to be used in proposals of public policies of urbanization of this city, enabling Teresina to “meet” its rivers again from the perception of the elements contextualizing the suitable sustainability for the man and for the environment in all regards of life.